Análise e readequação do projeto de drenagem do residencial Cristo Vive localizado no município de Tucuruí-PA - BOFF, Diogo (2022)
This study aims to analyze and propose an overhaul of the residential rainwater drainage system Cristo Vive in Tucuruí - PA. Integrant of the Federal Government's housing program Minha Casa Minha Vida, this building began in 2012 with the initial goal of offering 1,508 homes for low-income population registered in this program. The building of the residential was paralyzed in 2013 after a technical inspection of the engineering team of Caixa Econômica Federal - responsible for the supervision and financing of the work - note several problems of infrastructure and irregularities, removing granting the company responsible for its execution. The land where it was built the residences is quite rugged and did not receive proper leveling process. Thus, the streets of the build are quite steep, reaching more than 10% longitudinal of slope in some places and causing large flows and high speeds of stormwater runoff during rainfall on site. This factor, combined with the low efficiency of the drainage system, resulted in damage to several streets and building infrastructure elements. This study finds, through photographic survey that errors in the urban drainage system of rainwater were responsible for the damage to infrastructure of the building, which features mainly paving and sidewalks quite damaged by erosion, resulting from the flow of waters not captured. In addition to the damages caused, was found that a large amount of sediment is being carried by the water and deposited in the area of a igarapé downstream of the building, causing accelerated silting process. By the plan of original project drainage and topographic lifting of the streets, this work consists of, first, assess the mistakes of the residential drainage system, compared to the recommendations and instructions of the most accepted theoretical references in scientific area - once that no exist specific Brazilian rules that instruct this executive procedure. Was found errors both in the preparation of the project - observed in the original plan - as in the execution of system elements. Subsequently, was produced a new drainage project of rainwater for residential, with producing of sizing sheets of each element by following the theoretical framework for this. The main system corrections were positioning of components and changes in the type of used collecting mouths, aimed at adapting the ability to capture in accordance with the calculated flow rates and ensuring safety and drainage efficiency. The project developed aims an overhaul of the system providing for the reuse of some of the drainage elements previously used, and at the end of this work, there is the new plan of rainwater drainage system with the changes indicated.